Study of Cross-Linked Poly(N-vinyl-2-pyrrolidone) Gel and Its Uses in the Controlled Release of Antiinflammatory Drug Diclofenac Sodium - Ali Khan1, Farhat; Abbas2, Sudhair; Ahmad3, Bashir; M. Abdei-Salam4, Naser; Ullah5, Riaz (Asian Journal of Chemistry, 2014)
The objective of present study was to synthesize poly(N-vinyl-2-pyrrolidone) gel with different compositions, characterized and used as carrier for different of drugs. Three formulations with different ratios (drugs-hydrogel ratio 1:1, 1:2 and 1:3) were prepared. The released of drug from hydrogels followed both diffusion and erosion. The hydrogel was compressed with diclofenac sodium at different ratios (drugs-hydrogel ratio 1:1, 1:2 and 1:3). After being compressed, matrix tablets were put into dissolution medium in order to test the release mechanism of diclofenac sodium from compressed tablets and its release time. The sustainability of diclofenac sodium (1:1) was 5.5 h and the drug release from compressed tablets was 92 %. The sustainability of diclofenac sodium (1:2) was 8 h and the drug release from matrix tablets was 85 %. The results obtained at 1:3 showed 77 % of diclofenac sodium was released after 13 h. The present study revealed that drugs and hydrogel at 1:3 was proficient for supporting the diclofenac sodium for longer period of time as compared with other drug/polymer ratios (1:1 and 1:2).